Prospects of Implementing Mutual Legal Assistance Against Transnational Tax Crimes (Study of Reciprocal Agreements between Indonesia - Switzerland) - Lutfi, Khoirur Rizal; Pratiwi, Dian Khoreanita; Putri, Citraresmi Widoretno (Faculty of Law, Pembangunan Nasional Veteran Jakarta University, 2020)
This study aims to determine and understand the visibility of implementing a reciprocal agreement between Indonesia and Switzerland in the field of Tax Crimes and the steps that the two countries can take to optimize the role of the treaty. The method used in this research is the normative juridical method using secondary data with a statutory approach. This research uses descriptive-evaluative analysis. The results of this study indicate that the prospect of implementing a reciprocal agreement between Indonesia and Switzerland in the field of tax crimes could be an opening for mutual legal aid cooperation with other European countries. This agreement helps Indonesia return the country's wealth that was taken abroad by individuals who misuse state finances, especially in the field of taxation. The steps that can be taken by the two countries to optimize the role of the agreement are to mutually ratify and implement it into their respective national laws, currently Indonesia has ratified it through Law Number 5 of 2020 concerning Ratification of the Joint Legal Aid Agreement in Criminal Matters between the Republic of Indonesia and the Swiss Confederation, however, the ratification stage alone is not sufficient for a country that adheres to the dualism theory. Indonesia itself has not been consistent in implementing international agreements into national law. Indonesia must also have law enforcement officers who are reliable and have a global perspective, as well as the willingness to budget so that what has been promised can run as it should.Â